The Stele of a Veteran of Legio VII, Lucius Vetius Secundus, from Hrvace near Sinj (Archaeologia Adriatica, 2008)
The article discusses an unpublished monument of Lucius Vetius Secundus, a veteran of the 7th legion, who while alive erected a funerary monument to himself and another two members of his family. The veteran was originally from the city of Libarna, for which as yet we do not have many confirmations in epigraphy. The inscription is mostly legible, but could not be read in some places, so a reconstruction is suggested. The tombstone supplements in all aspects the epigraphic analyses of testimony discovered to the present for legio VII in the region of the Roman province of Dalmatia.
Keywords: 7th legion; Aequum; Tilurium; Libarna; veteran